Fatty acids and lipid mediators in inflammatory bowel disease: from mechanism to treatment - Yan, Dong; Ye, Shuyu; He, Yue; Wang, Sidan; Xiao, Yi; Xiang, Xin; Deng, Minzi; Luo, Weiwei; Chen, Xuejie; Wang, Xiaoyan (Frontiers in Immunology, 2023)
Inflammatory Bowel Disease (IBD) is a chronic, relapsing inflammatory disorder of the gastrointestinal tract. Though the pathogenesis of IBD remains unclear, diet is increasingly recognized as a pivotal factor influencing its onset and progression. Fatty acids, essential components of dietary lipids, play diverse roles in IBD, ranging from anti-inflammatory and immune-regulatory functions to gut-microbiota modulation and barrier maintenance. Short-chain fatty acids (SCFAs), products of indigestible dietary fiber fermentation by gut microbiota, have strong anti-inflammatory properties and are seen as key protective factors against IBD. Among long-chain fatty acids, saturated fatty acids, trans fatty acids, and ω-6 polyunsaturated fatty acids exhibit pro-inflammatory effects, while oleic acid and ω-3 polyunsaturated fatty acids display anti-inflammatory actions. Lipid mediators derived from polyunsaturated fatty acids serve as bioactive molecules, influencing immune cell functions and offering both pro-inflammatory and anti-inflammatory benefits. Recent research has also highlighted the potential of medium-and very long-chain fatty acids in modulating inflammation, mucosal barriers, and gut microbiota in IBD. Given these insights, dietary intervention and supplementation with short-chain fatty acids are emerging as potential therapeutic strategies for IBD. This review elucidates the impact of various fatty acids and lipid mediators on IBD and delves into potential therapeutic avenues stemming from these compounds.